Family therapy review : contrasting contemporary models - Rambo, Anne Hearon (Routledge, 2013)
"This unique text uses one common case to demonstrate the applications of a wide range of family therapy models. Readers will find it useful when studying for the national family therapy licensing exam, which requires that exam takers be able to apply these models to case vignettes. The authors, all of whom are practicing family therapists, apply their chosen model of family therapy to a single, hypothetical case to highlight what each model looks like in practice. Beginning therapists will find the exposure to new ideas about therapy useful, and will be better able to establish which approaches they want to explore in more depth. Experienced therapists and supervisors will find it useful to understand what "those other family therapists" are doing, and to meet the challenge of supervising those from different perspectives. Family Therapy Review is the practical tool therapists need to make sense of the field, and meet the varied challenges their clients present"--